Nickel-L-leucine framework (MOF): synthesis, structural characterization, and potential applications in biological studies - Mehvish Kiran; Khawaja Ansar Yasin; Sirajul Haq; Khaled Elmnasri; Fethi Ben Abdallah; Manel Ben Ali; Amreen Shah; Amor Hedfi; Ezzeddine Mahmoudi (Materials Research Express, 2023)
The microbial resistance to antibiotics and the generation of free radicals inside as a result of different oxidative processes are modern global challenges for researchers. The exploration of MOFs as an antibacterial agent against pathogenic bacteria and as an antioxidant agent to scavenge free radicals as countermeasures to alleviate these problems. For this purpose, the metal organic framework (MOF), composed of L-leucine as a linker and nickel as a metal, was synthesized via a convenient, one-pot process under reflux conditions. The products formed were characterized through different techniques, including N _2 adsorption experiments, Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), scanning electron microscopy (SEM), and X-ray diffraction (XRD). The physicochemical analysis shows that the MOF has a crystalline nature with a surface area of 129 (±5) m ^2 /g and a pore size of 1.95 nm. The synthesized MOF was then subjected to antibacterial activity, and the high activity was recorded against S. aureus . The dose-dependent antioxidant study shows the activity increases with increasing the concentration of the MOF. However, both the antibacterial and antioxidant activities were found to be less than those of the standard drugs (clindamycin and ascorbic acid).